Effects of Cryopreservation on the Cell Viability, Proliferative Capacity and Neuronal Differentiation Potential of Canine Bone Marrow Stromal Cells - EDAMURA, Kazuya (The Japanese Society of Veterinary Science, 2013)
We investigated the cell viability, proliferative capacity and neuronal differentiation potential of canine bone marrow stromal cells (BMSCs) after cryopreservation. BMSCs were cryopreserved using cryoprotectant solutions with 10% DMSO and 10% FBS (DF group) or without DMSO and FBS (DF-free group); fresh BMSCs were used as a control. The cell viability and proliferative capacity of BMSCs were similar in the DF-free and control groups, while those in the DF group were lower. In all groups, BMSCs differentiated into neuron-like cells that stained positive against neuron markers, and the mRNA expression levels of neuron markers increased after neuronal induction. In conclusion, cryopreservation with DF-free cryoprotectant solution did not diminish the cell viability, proliferative capacity or neuronal differentiation potential of canine BMSCs.